Coated Paper
A coated paper with a PHBH and EVA coating layer addresses cracking issues by enhancing bending resistance and maintaining structural integrity, suitable for packaging applications.
Patent Information
- Application Number
- JP2024161912
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2044-09-19
AI Technical Summary
Existing coated papers with PHBH coatings are prone to cracking during folding, leading to reduced strength and shape integrity, especially when exposed to moisture, limiting their use in packaging applications.
A coated paper with a coating layer containing PHBH and EVA, where EVA has specific tensile strength and elongation properties, is developed to enhance crack resistance and bending resistance.
The coated paper exhibits improved resistance to cracking and maintains structural integrity during folding and exposure to moisture, making it suitable for packaging uses such as boxes and blister packs.
Smart Images

Figure 0007607175000001 
Figure 0007607175000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated paper having a coating layer containing PHBH. [Background technology]
[0002] In recent years, efforts have begun to prevent environmental destruction caused by plastic waste, and there is a demand to replace disposable plastic products with materials that have a smaller impact on the environment. Alternative materials to plastic include biodegradable plastics, wood, paper, etc. Aliphatic polyesters such as polylactic acid and polycaprolactone are known as biodegradable plastics. However, aliphatic polyesters have the problem that they take a long time to biodegrade at low temperatures and decompose slowly in natural environments such as the ocean.
[0003] Poly(3-hydroxybutyrate) resins are microbially produced thermoplastics that are highly degradable under aerobic and anaerobic conditions, and have the remarkable ability to be decomposed by microorganisms in a short period of time even in water such as the ocean. Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (hereinafter also referred to as PHBH), a copolymer of 3-hydroxybutyrate and 3-hydroxyhexanoate, has attracted attention for its biodegradability and resin properties.
[0004] Patent Document 1 proposes a coated paper with few coating defects, which has a coating layer containing PHBH and an adhesive on at least one surface of a paper base material, and in which the solid mass ratio of PHBH to adhesive in the coating layer is 99.9 / 0.1 to 60.0 / 40.0, and describes that the coated paper can be used as heat seal paper, waterproof paper, oil-resistant paper, etc.
[0005] Plastic-free paper blister packs are used to package stationery, toothbrushes, and the like and display them in stores (Patent Document 2). When a package such as a paper blister pack was manufactured by folding the heat seal paper described in Patent Document 1 using a thick paper base material, a problem occurred in which cracks occurred at the folded portion of the coating layer. If cracks occurred at the folded portion of the package, water from rain or the like would easily seep into the inside, so that the strength of the package would be easily reduced when it gets wet, and the three-dimensional shape of the package would easily collapse. In addition, paper blister packs are sometimes stored in their original packs after use when traveling, but if something with water on it is included, the shape would also easily collapse. As a method for suppressing cracks during folding, a method of adjusting the tensile breaking elongation and moisture content of the paper base material is known (paragraphs 0028-0029 of Patent Document 3). However, the tensile breaking elongation and moisture content of the paper base material are controlled in the papermaking process, and it is not possible to use any available paper base material. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2021 / 256381 [Patent Document 2] Japanese Patent Application Publication No. 07-172465 [Patent Document 3] Patent Publication No. 2022-089429 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a coated paper that can be used with any paper base material and is less susceptible to cracking during folding. [Means for solving the problem]
[0008] The means for solving the problems of the present invention are as follows. 1. Basis weight 100g / m 2The paper substrate has a coating layer containing PHBH and EVA on at least one surface thereof, The coating amount (dry weight) of the coating layer is 5 g / m per side. 2 That's all. The coating layer contains 5 parts by mass or more and 120 parts by mass or less of the EVA per 100 parts by mass of the PHBH, The coated paper is characterized in that the EVA has a tensile strength of 4.5 to 25.0 MPa and an elongation of 400 to 800%. 2. The coated paper according to 1, wherein the molar ratio of ethylene to vinyl acetate in the EVA (ethylene:vinyl acetate, total 100) is 5:95 to 45:55. 3. Coated paper according to 1 or 2, characterized in that the glass transition temperature (Tg) of the EVA is -40°C or higher and 10°C or lower. 4. A packaging body having the coated paper described in any one of 1. to 3. Effect of the Invention
[0009] The coated paper of the present invention is less susceptible to cracking due to folding and has excellent flex resistance. The coated paper of the present invention is suitable for producing packaging bodies such as boxes and paper blister packs by folding and heat sealing. Since the occurrence of cracks is suppressed, packaging bodies using the coated paper of the present invention are less likely to lose strength even when wet and are less likely to lose their three-dimensional shape. The coated paper of the present invention contains a high proportion of biodegradable materials and will decompose quickly even if it is released into the environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The coated paper of the present invention has a basis weight of 100 g / m 2 The paper substrate has a coating layer containing PHBH and EVA on at least one surface thereof, The coating amount (dry weight) of the coating layer is 5g / m per side. 2 That's all. The coating layer contains 5 parts by mass or more and 120 parts by mass or less of EVA per 100 parts by mass of PHBH, The EVA has a tensile strength of 4.5 to 25.0 MPa and an elongation of 400 to 800%. In this specification, the tensile strength and elongation are values evaluated at 3.4 and 3.5, respectively, according to JIS-K-6251: 2017. In addition, in this specification, the expression "A to B" (A and B are numerical values or ratios) means a numerical range including A and B.
[0011] The coated paper of the present invention may have a coating layer on one outermost surface, or may have coating layers on both outermost surfaces, and may also have other layers between the paper substrate and the coating layer, such as an anchor layer, a water vapor barrier layer, a gas barrier layer, an ink receiving layer, etc.
[0012] (Paper base material) The paper base material is a sheet mainly made of pulp, and is obtained by papermaking a paper stock containing fillers, various auxiliaries, etc. Examples of pulp include chemical pulps such as bleached hardwood kraft pulp (LBKP), bleached softwood kraft pulp (NBKP), unbleached hardwood kraft pulp (LUKP), unbleached softwood pulp (NUKP), sulfite pulp, and other chemical pulps, mechanical pulps such as stone grind pulp and thermomechanical pulp, wood fibers such as deinked pulp and waste paper pulp, and non-wood fibers obtained from kenaf, bamboo, hemp, and the like, and one or more of these can be used in appropriate combination. Among these, it is preferable to use chemical pulp of wood fiber or mechanical pulp of wood fiber, and it is more preferable to use chemical pulp of wood fiber, for reasons such as the fact that foreign matter is unlikely to be mixed into the paper base material, that discoloration is unlikely to occur over time when recycled as waste paper raw material, that the surface texture is good when printed due to its high whiteness, and that its value in use is particularly high when used as a packaging material. Specifically, the blending amount of wood fiber chemical pulp such as LBKP or NBKP relative to the total pulp is preferably 80 mass % or more, more preferably 90 mass % or more, even more preferably 95 mass % or more, and most preferably 100 mass %.
[0013] Examples of fillers that can be used include inorganic fillers such as talc, kaolin, calcined kaolin, clay, heavy calcium carbonate, light calcium carbonate, white carbon, zeolite, magnesium carbonate, barium carbonate, titanium dioxide, zinc oxide, silicon oxide, amorphous silica, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, barium sulfate, and calcium sulfate, and organic fillers such as urea-formalin resin, polystyrene resin, phenolic resin, and hollow microparticles. Note that fillers are not essential materials and may not be used.
[0014] Examples of various auxiliary agents include sizing agents such as rosin, alkyl ketene dimer (AKD), alkenyl succinic anhydride (ASA), polyacrylamide polymers, polyvinyl alcohol polymers, cationic starch, various modified starches, urea-formaldehyde resin, melamine-formaldehyde resin, and other dry strength agents, wet strength agents, retention agents, drainage improvers, coagulants, aluminum sulfate, bulking agents, dyes, fluorescent brighteners, pH adjusters, defoamers, UV inhibitors, anti-fading agents, pitch control agents, slime control agents, and the like, and can be selected and used as appropriate as needed.
[0015] The surface of the paper substrate may be treated with various chemicals. Examples of chemicals include oxidized starch, hydroxyethyl etherified starch, enzyme-modified starch, polyacrylamide, polyvinyl alcohol, surface sizing agents, water-resistant agents, water retention agents, thickeners, and lubricants, and these may be used alone or in combination of two or more. Furthermore, these various chemicals may be used in combination with pigments. Examples of pigments include inorganic pigments such as kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate salts, colloidal silica, and satin white, and organic pigments such as solid, hollow, and core-shell types may be used alone or in combination of two or more.
[0016] In the present invention, the basis weight of the paper base material is 100 g / m 2The basis weight is 100g / m 2 A paper base material having a basis weight of 500 g / m or more is suitable for producing a package by folding. There is no particular upper limit on the basis weight of the paper base material, but for example, if the paper base material becomes too thick, folding processing may become difficult. 2 The following is more preferred: The density of the paper base material can be appropriately selected depending on the desired qualities and ease of handling, but is usually 0.5 g / cm 3 More than 1.0g / cm 3 The following are preferred: In the present invention, the paper base material may be either a paper consisting of only a single paper layer or a multi-layer paper having two or more paper layers. When the paper base material is a multi-layer paper, the paper materials, basis weights, etc. of each paper layer may be the same or different.
[0017] The method for producing (making) the paper base material is not particularly limited, and any known production (making) method or papermaking machine can be selected, such as a Fourdrinier papermaking machine, a cylinder papermaking machine, a short wire papermaking machine, or a twin-wire papermaking machine such as a gap former type or a hybrid former type (on-top former type).The pH during papermaking may be in the acidic range (acidic papermaking), pseudo-neutral range (pseudo-neutral papermaking), neutral range (neutral papermaking), or alkaline range (alkaline papermaking), and after papermaking in the acidic range, an alkaline agent may be applied to the surface of the paper layer. Furthermore, when treating the surface of a paper substrate with a chemical, the method of surface treatment is not particularly limited, and known coating devices such as a rod metering size press, a pond type size press, a gate roll coater, a spray coater, a blade coater, or a curtain coater can be used.
[0018] (Coating layer) The coating layer is located on at least one outermost surface of the coated paper, contains at least PHBH and EVA, and has a coating weight (dry mass) of 5 g / m per side. 2 The content of EVA is 5 parts by mass or more and 120 parts by mass or less per 100 parts by mass of PHBH.
[0019] <phbh> PHBH is a copolymer of 3-hydroxybutyrate (hereinafter also referred to as 3HB) and 3-hydroxyhexanoate (hereinafter also referred to as 3HH), and is a biodegradable resin known to be produced by microorganisms. In the present invention, the PHBH used may be derived from microorganisms or petroleum resources, but it is preferable to use the PHBH derived from microorganisms in terms of reducing the environmental load.
[0020] Microorganisms that produce PHBH are not particularly limited as long as they accumulate PHBH intracellularly, but examples include bacteria of the genus Alcaligenes, such as A. lipolytica, A. eutrophus, and A. latus, as well as bacteria of the genus Pseudomonas, Bacillus, Azotobacter, Nocardia, and Aeromonas. Among them, in terms of productivity of PHBH, strains such as Aeromonas caviae, and Alcaligenes eutrophus AC32 into which genes of PHA synthase group have been introduced (Accession No. FERM BP-6038, Date of deposit on August 7, 1997, National Institute of Advanced Industrial Science and Technology, International Patent Organism Depositary, Address: Central 6, 1-1-1 Higashi, Tsukuba-shi, Ibaraki-ken, Japan) (J. Bacteriol., 179, pp. 4821-4830 (1997)) are particularly preferred. A method for obtaining PHBH from Aeromonas caviae, a microorganism of the Aeromonas genus, is disclosed, for example, in Japanese Patent Application Laid-Open No. 05-093049. These microorganisms are used by culturing them under appropriate conditions to accumulate PHBH in the cells. The carbon source and culture conditions used in the culture can be obtained according to the methods described in JP-A-05-093049, JP-A-2001-340078, etc., but are not limited thereto.
[0021] The composition ratio (mol%) of PHBH is preferably 3HB:3HH=97:3 to 75:25, more preferably 95:5 to 85:15. If the composition of 3HH is less than 3 mol%, the properties of PHBH become similar to those of 3HB homopolymer, resulting in loss of flexibility and an excessively high film-forming processing temperature, which is undesirable. If the composition of 3HH exceeds 25 mol%, the crystallization rate becomes too slow to be suitable for film-forming processing, and the degree of crystallization decreases, making the resin flexible and decreasing the bending modulus. The composition ratio of PHBH can be measured by centrifuging the aqueous dispersion and then drying the powder obtained by NMR analysis. Microbial PHBH is a random copolymer. To adjust the molar ratio of the copolymer, there are several methods, such as selecting the bacterial cells, selecting the carbon source as the raw material, blending with PHBH of different molar ratios, and blending with 3HB homopolymer.
[0022] The mass average molecular weight of PHBH is preferably 50,000 to 1,500,000. When the mass average molecular weight of PHBH is within this range, a film can be formed at a low temperature when PHBH is applied, and a film with excellent mechanical properties can be obtained when PHBH is laminated. The mass average molecular weight of PHBH is more preferably 100,000 to 500,000, and even more preferably 150,000 to 450,000. The mass average molecular weight of PHBH can be determined by gel permeation chromatography (GPC, such as "Shodex GPC-101" manufactured by Showa Denko K.K.) using polystyrene gel (such as "Shodex K-804" manufactured by Showa Denko K.K.) in a column, using chloroform as the mobile phase, and converting it into a polystyrene-equivalent molecular weight. The measurement sample is a powder obtained by centrifuging an aqueous dispersion containing PHBH and then drying it.
[0023] The average particle size of PHBH is preferably 0.1 to 50 μm. PHBH with an average particle size of less than 0.1 μm is difficult to produce by microbial production, and even when obtained by chemical synthesis, a microparticulation operation is required. If the average particle size exceeds 50 μm, uneven coating may occur on the surface when a coating liquid containing PHBH is applied. The average particle size of PHBH is more preferably 0.5 to 10 μm. The average particle size of PHBH refers to the particle size corresponding to 50% accumulation of all particles measured by adjusting an aqueous suspension of PHBH to a predetermined concentration using a general-purpose particle sizer such as a Microtrack particle sizer (manufactured by Nikkiso, FRA).
[0024] <eva> The EVA used in the present invention has a tensile strength of 4.5 to 18.5 MPa and an elongation of 400 to 800%. The coated paper of the present invention has excellent crack resistance, although the mechanism is unclear, because the coating layer contains 5 to 120 parts by mass of EVA that satisfies specific tensile strength and elongation per 100 parts by mass of PHBH. From the viewpoint of crack resistance, the tensile strength of the EVA is preferably 5.0 to 18.5 MPa. The elongation of the EVA is preferably 420 to 700%, more preferably 650% or less.
[0025] EVA (ethylene vinyl acetate copolymer) is a copolymer having ethylene and vinyl acetate as monomers, and may further have other monomers as monomers. However, the EVA of the present invention is not saponified and does not have vinyl alcohol units resulting from saponification of vinyl acetate units. When EVA has other monomers as monomers, the content of the structural units derived from other monomers relative to the entire EVA is preferably 30% by mass or less. This content is not particularly limited as long as it does not impair the effects of the present invention, and can be, for example, 20% by mass or less, 10% by mass or less, 5% by mass or less, 3% by mass or less, 1% by mass or less, etc.
[0026] The molar ratio of ethylene to vinyl acetate in EVA (structural units derived from ethylene:structural units derived from vinyl acetate, also expressed as ethylene:vinyl acetate, the total being 100) is preferably 5:95 to 45:55, more preferably 7:93 to 43:57, even more preferably 10:90 to 40:60, and even more preferably 20:80 to 40:60, from the viewpoint of crack resistance. Moreover, from the viewpoint of crack resistance, the glass transition temperature (Tg) of EVA is preferably −40° C. or higher and 10° C. or lower, more preferably −35° C. or higher, even more preferably −30° C. or higher, more preferably 5° C. or lower, and even more preferably 0° C. or lower. In this specification, the glass transition temperature means the midpoint glass transition temperature measured in accordance with JIS K 7121-1987.
[0027] The coated paper of the present invention has a coating layer containing 5 to 120 parts by weight of EVA per 100 parts by weight of PHBH. The coating layer has excellent crack resistance due to the PHBH and EVA content in this ratio. The ratio of EVA per 100 parts by weight of PHBH is preferably 7 parts by weight or more, more preferably 10 parts by weight or more, and is preferably 110 parts by weight or less, more preferably 105 parts by weight or less.
[0028] The coating layer only needs to contain PHBH and EVA, and may also contain other thermoplastic resins and inorganic pigments. <Other thermoplastic resins> As the other thermoplastic resin, any resin having heat sealability at the temperature at which PHBH is fused can be used without any particular limitation. However, preferred are biodegradable resins such as aliphatic polyester-based resins such as polycaprolactone, polybutylene succinate adipate, polybutylene succinate, and polylactic acid, and aliphatic aromatic polyester-based resins such as polybutylene adipate terephthalate and polybutylene azelate terephthalate.
[0029] When the coating layer contains another thermoplastic resin, the total proportion of PHBH and EVA to the total thermoplastic resin contained in the coating layer is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, even more preferably 99% by mass or more, and most preferably 100% by mass.
[0030] <Inorganic pigments> As the inorganic pigment, those used for coating on paper can be used without any particular limitation, and examples thereof include kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, bentonite, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate salts, colloidal silica, satin white, etc., and one or more of these can be used. Among these, one or more of kaolin, heavy calcium carbonate, light calcium carbonate, mica, talc, and bentonite are preferred.
[0031] From the viewpoint of the fixation of the coating layer, the inorganic pigment preferably has a volume 50% average particle size (D50, hereinafter also referred to as "average particle size") of 6.0 μm or less, measured by a laser diffraction / scattering method. Examples of measuring devices for the laser diffraction / scattering method include a particle size distribution measuring device "Partica" from Horiba, Ltd. and a particle size distribution measuring device "MASTER SIZER S" from Malvern Instruments. From the viewpoint of the fixation of the coating layer, the average particle size of the inorganic pigment is more preferably 5.0 μm or less, even more preferably 4.0 μm or less, even more preferably 3.0 μm or less, and even more preferably 2.0 μm or less. There is no particular lower limit for the average particle size of the inorganic pigment, but from the viewpoint of dispersibility, for example, it is preferably 0.1 μm or more, and more preferably 0.2 μm or more. When two or more inorganic pigments are contained, it is preferable that the average particle size of at least one of the inorganic pigments is within the above-mentioned numerical range, and the proportion of the inorganic pigments satisfying this average particle size relative to the total inorganic pigments is preferably 50 mass % or more, and more preferably 70 mass % or more.
[0032] When the coating layer contains an inorganic pigment, the solid content mass ratio of PHBH to inorganic pigment (PHBH: inorganic pigment, total 100) is preferably 90:10 to 0.01:99.99. By further blending an inorganic pigment into a coating liquid containing PHBH and EVA, the fixation of the resulting coating layer is improved. Although the mechanism is unclear, the present inventors speculate that this is because inorganic pigments have better thermal conductivity than organic PHBH and adhesives, so that the inorganic pigments quickly rise in temperature when heated, and this heat is transferred from the inorganic pigment to PHBH, so that PHBH is sufficiently heated and melted, making it easy to form a film. The solid content mass ratio of PHBH to inorganic pigment (PHBH:inorganic pigment, total 100) is more preferably 70:30 to 1:99, further preferably 60:40 to 2:98, and even further preferably 50:50 to 3:97, from the viewpoint of fixation of the coating layer.
[0033] The coating layer may contain, in addition to PHBH, EVA, other thermoplastic resins, and inorganic pigments, other water-soluble resins and water-dispersible resins, and may further contain, as necessary, various auxiliaries that are blended into coating solutions in the papermaking field, such as dispersants, viscosity improvers, defoamers, water-resistant agents, pH adjusters, cationic resins, anionic resins, UV absorbers, metal salts, lubricants, coloring dyes, and pigments.
[0034] (Manufacturing method) The coating layer can be produced by a conventionally known coating method. For example, the coating device may be a blade coater, a bar coater, a roll coater, an air knife coater, a reverse roll coater, a curtain coater, a spray coater, a size press coater, a gate roll coater, etc. In addition, the coating system may be an aqueous coating using a solvent such as water, a solvent coating using a solvent such as an organic solvent, etc., and the aqueous coating is preferable.
[0035] The coating amount (dry mass) of the coating layer is 5g / m per side. 2 This coating amount is 5g / m 2 If the coating layer is less than 6 g / m, cracks are likely to occur in the coating layer during folding. 2 More preferably, 10 g / m 2 The upper limit of the coating amount is not particularly limited, but is, for example, 50 g / m 2 The coating weight is preferably 50 g / m or less. 2 Above this value, the crack resistance saturates and hardly improves any further, and the material cost increases, as well as the drying load during coating increases.
[0036] The coated paper of the present invention has a heat seal strength of 180°C at a pressure of 0.2MPa (20.0N / cm) measured in accordance with JIS Z1707:2019 7.4 "Heat seal strength test". 2 ), the heat seal strength when heat-sealed with a pressure application time of 1.0 second and then T-peeled is preferably 4.0 N / 15 mm or more, more preferably 5.0 N / 15 mm or more, even more preferably 6.0 N / 15 mm or more, and even more preferably 6.5 N / 15 mm or more.
[0037] ·Packaging The coated paper of the present invention has excellent folding processability and heat sealability, and is suitable for processing into a package. When the coated paper of the present invention is used for a package, the shape of the package is not particularly limited, but examples thereof include an aseptic container for filling beverages such as milk and juice as described in JP 2005-306424 A, a brick pack container as described in JP 2004-026285 A, a rectangular or square tubular packaging container with an extraction device for filling shampoo, conditioner, etc. as described in JP 2022-103436 A, a web corner package of an irregular shape as described in JP 2014-227187 A, a paper container containing granular materials such as gum and chocolate confectionery as described in JP 06-025170 A, and a flat and elongated paper blister pack as described in JP 07-172465 A. EXAMPLES
[0038] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, parts and % are by mass, respectively, unless otherwise specified.
[0039] (Evaluation method) Tape pick The prepared coated paper was placed on a horizontal table and conditioned for at least 24 hours (conditions: 23°C, humidity 50%), after which a 12 mm wide mending tape (3M Japan, Scotch (registered trademark) Mending Tape 810-1-12) was applied to the coating layer surface of the coated paper, and a 130 mm wide, 1.8 kg weight rubber roller was reciprocated 20 times under its own weight on the mending tape to make the mending tape adhere to the coating layer surface. Immediately afterwards, the mending tape was vigorously peeled off, and the ratio of the area where the coating layer was peeled off from the paper substrate surface by adhering to the mending tape (area of interface destruction) to the area where the mending tape was applied, or the ratio of the area where the paper substrate was destroyed by a part of the paper substrate adhering to the mending tape together with the coating layer (area of internal destruction of the paper substrate) was calculated, and the adhesion to the paper substrate was evaluated according to the following criteria. If the evaluation is 5 or 4, there is no problem in practical use. 5: No peeling 4: 0-10% or less of the adhesive surface peels off 3: Less than 10-50% of the adhesive surface peels off 2: Less than 50-90% of the adhesive surface has peeled off 1: 90-100% of the adhesive surface peels off
[0040] ·Bending resistance The paper base material was placed on the inside and the coating layer on the outside, and the paper was folded in the MD (folds perpendicular to the MD) or CD (folds perpendicular to the CD), and the folded portion was pressed with a 400g roller going back and forth 10 times under its own weight. After that, 0.05% New Coccin dye solution was applied to the folded portion, and after leaving it to stand for 30 seconds, it was wiped off with a JK wiper, and the penetration was evaluated according to the following criteria. Evaluation samples are shown in Table 1. A rating of 5 to 3 is acceptable for practical use. 5: No penetration 4: Penetration into the coating surface and base paper layer confirmed in less than 5% of the folded area 3: Confirmed penetration into the coating surface and base paper layer in 5% to 30% of the folded area 2: Confirmation of penetration into the coating surface and base paper layer in 30% to less than 70% of the folded area 1: Check that the coating has penetrated into the surface layer and base paper layer in 70% or more of the folded area.
[0041] [Table 1]
[0042] Heat seal strength The test was performed in accordance with JIS Z1707:2019 7.4 "Heat seal strength test". Two square test pieces with sides of 100 mm were cut from the resulting coated paper, and the coating layers were brought into contact with each other and pressed at temperatures of 130°C, 140°C, 150°C, or 160°C under a pressure of 0.2 MPa (20.0 N / cm 2 ), heat-sealed with pressure for 1.0 second, and then left to stand for 24 hours in an environment of 23°C and 50% humidity. A measurement sample with a long side of 100 mm and a short side of 15 mm was then cut out from the heat-sealed 100 mm square test piece. The peeled long edge was then clamped between the upper and lower jigs of a vertical tensile testing machine (Tensilon, manufactured by A&D Corporation), and the peel strength, i.e., HS strength (N / 15 mm), was measured while peeling the measurement sample (T-type) from the long edge side at a speed of 200 mm / min. The peeled surface was visually observed and evaluated according to the following criteria. The measurement was performed twice, and the peel strength was shown as the average value. If the evaluation results differed from those obtained by visual observation, Show both. 〇: Breakage on the entire heat-sealed surface △: Partial damage to the heat-sealed surface ×: Peeling occurs between coating layers (no material breakage) -: No heat seal
[0043] (material) Paper base material: Nippon Paper Industries, basis weight 220g / m 2 Cup base paper, CUP-HD PHBH: Kaneka Corporation, mass average molecular weight 200,000 EVA1: Sumika Chemtex Co., Ltd., S-400HQ: tensile strength 12.7 MPa, elongation 550%, ethylene:vinyl acetate = 20:80, Tg 0°C, EVA2: Sumika Chemtex, S-305HQ: tensile strength 18.0MPa, elongation 420%, ethylene:vinyl acetate=10:90, Tg7℃ EVA3: Sumika Chemtex, S-408HQE: Tensile strength 5.0MPa, elongation 650%, ethylene:vinyl acetate=40:60, Tg-30℃ EVA4: Sumika Chemtex, S-355HQ: tensile strength 20.6MPa, elongation 420%, ethylene:vinyl acetate=10:90, Tg10℃ EVA5: Sumika Chemtex, S-401HQ: tensile strength 6.2MPa, elongation 850%, ethylene:vinyl acetate=30:70, Tg-18℃
[0044] (Formation of coating layer) A coating solution with a solid content of 40% by mass was obtained by mixing and stirring PHBH, EVA or PVA in the parts by mass shown in Table 1. In Table 1, the values in parentheses for EVA indicate, from the left, tensile strength, elongation, ethylene:vinyl acetate molar ratio, and Tg. The coating liquid was applied onto one side of the paper substrate using a bar blade method so as to obtain the dry mass per side shown in Table 1. The substrate was then dried at 105°C for 1 minute and then heat-treated at 140°C for 1 minute to form a coating layer on the outermost surface of one of the paper substrates.
[0045] [Table 1]
[0046] The coated papers obtained in Examples 1 to 4 using EVA having a tensile strength of 4.5 to 20.6 MPa and an elongation of 400 to 800% were excellent in flex resistance. In contrast, Comparative Example 1 in which only PHBH was applied, Comparative Example 2 in which EVA not satisfying the specific tensile strength and elongation was used, and Comparative Example 3 in which only EVA having a tensile strength of 4.5 to 20.6 MPa and an elongation of 400 to 800% was applied were poor in flex resistance. Furthermore, it was found from Examples 1 and 5 to 8 that the flex resistance tended to improve as the ratio of EVA to 100 parts by mass of PHBH increased, and from Examples 1 and 9 to 11 that the coating amount (dry weight) of the coating layer increased.< / eva> < / phbh>
Claims
1. Basis weight 100g / m 2 The paper substrate has a coating layer containing PHBH and EVA on at least one surface thereof, The coating amount (dry weight) of the coating layer is 5 g / m per side. 2 That's all. The coating layer contains 5 parts by mass or more and 120 parts by mass or less of the EVA per 100 parts by mass of the PHBH, The coated paper is characterized in that the EVA has a tensile strength of 4.5 to 25.0 MPa and an elongation of 400 to 800%.
2. 2. The coated paper according to claim 1, characterized in that the molar ratio of ethylene to vinyl acetate in the EVA (ethylene:vinyl acetate, total 100) is 5:95 to 45:
55.
3. 3. The coated paper according to claim 1, wherein the EVA has a glass transition temperature (Tg) of -40°C or higher and 10°C or lower.
4. A packaging material comprising the coated paper according to claim 1 or 2.
Citation Information
Patent Citations
Paper-made blister pack
JP1995172465A
Coated paper
JP2021195717A
Packaging container
JP2022089429A
Base paper for metallized paper, metallized paper, packaging bag, laminate, and paper container for liquid
JP2024008816A
Paper laminate
WO2021106926A1
